Tanfīż Manhaj al-Ta’allum al-Mustaqil fī Ta’lim al-Lugah al-‘Arabiyyah Liṭullab al-Madrasah al-Ṡānawiyyah - Nurwidiya, Salysa; Harisca, Rodhi; Khoirurrijal, Khoirurrijal (Aphorisme: Journal of Arabic Language, Literature, and Education, 2024)
This qualitative study explores the implementation of an independent learning curriculum for teaching Arabic to eighth-grade students at Muhammadiyah Ahmed Dahlan Metro Middle School in the academic year 2023/2024 AD. The study includes all eighth-grade students as the population, with a purposive sample for detailed analysis. Data from interviews, observations, and document analysis ensure a comprehensive understanding. Data collection methods include structured interviews, classroom observations, and document analysis. Thematic analysis is used to identify key themes and patterns related to curriculum implementation. Findings indicate a five-stage independent curriculum implementation process: diagnostic assessment, planning, learning, assessment, and reflection/evaluation. Challenges include teacher difficulties in selecting teaching methods, lack of a grading system, student motivation issues, and resistance to changing assessment methods. Strategies to enhance the curriculum include school policy adjustments, teacher training, infrastructure improvements, and ongoing monitoring of teaching activities.